The Basis of Issuance and Reasons for Revocation of the Attorney General's Guideline No. 7 of 2020 - Ahmad Firjatullah Farhan; Zulhidayat Zulhidayat; Hamonangan Albariansyah (Faculty of Law, Universitas Lampung, 2025)
This study examines two fundamental issues concerning the Attorney General’s Guideline No. 7 of 2020, which regulates the granting of permission for the summoning, examination, search, arrest, and detention of prosecutors suspected of committing criminal acts. The primary issues analyzed are: (1) the juridical and philosophical foundations underlying the issuance of the Guideline, and (2) the legal basis and substantive reasons for its subsequent revocation. This research employs a normative legal research method, using statutory, conceptual, and philosophical approaches by analyzing laws and regulations, legal doctrines, and relevant scholarly opinions. Juridically, the issuance of the Guideline was grounded in Article 8 paragraph (5) of Law Number 11 of 2021 concerning the Prosecutor’s Office of the Republic of Indonesia, which requires the Attorney General’s authorization for law enforcement actions against prosecutors. This provision aims to prevent arbitrary criminalization and protect prosecutorial independence. Philosophically, the Guideline was intended to provide procedural legal protection for prosecutors in their role as dominus litis, enabling them to perform their duties independently and free from intimidation while preserving the dignity of the prosecutorial profession. However, the Guideline was revoked shortly after its enactment through the Decree of the Attorney General of the Republic of Indonesia Number 163 of 2020 due to political, legal, and sociological considerations, particularly public concerns regarding equality before the law and the potential for prosecutorial impunity. This study concludes that the issuance and revocation of the Guideline reflect an inherent tension between the need for institutional protection of prosecutors and public demands for transparency, accountability, and equality before the law within Indonesia’s criminal justice system.